(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article presents the results of studies on the study of the electrical resistance of the degree of damage Rd.d (an assessment indicator of the condition of living tissues) that occurs when one of the following factors changes: U - discharge voltage; kV; τti - processing time, s; I - discharge current, A; F - shape and size of rhizomes; h - interelectrode space (the distance between the positive and negative electrodes where the plant tissue of the humai is located); C is the capacity of the storage capacitor, F; P - chemical and biological components in the electric pulse treatment of weeds. The research examined the data U, I, τti and Rd.d, which contain variable values and have the most significant indicators. Histograms were constructed to visualize the distribution of each variable and a regression model line was constructed covering all combinations of variables U, I and τti to the third degree, which allows one to assess their influence on the dependent variable Rd.d.